Genetic contribution of breast cancer genes in women of black African origin - Ndiaye, Rokhaya; Diop, Jean Pascal Demba; Dem, Ahmadou; Dieye, Alioune (Frontiers in Genetics, 2023)
Breast cancer (BC) is an increasing public health issue worldwide. BC incidence and mortality rates are rising in transitioning countries in Africa, with the most rapid increase occurring in Sub-Saharan Africa (SSA). Female BC represents 25.8% of all cancer diagnosis in SSA. Early age at onset, high grade and triple negative tumors are hallmarks of BC in this region, associated with germline pathogenic variants in susceptibility genes. While several genes have been associated with genetic predisposition (BRCA1, BRCA2, PALB2, TP53, PTEN, CDH1, STK11, ATM, CHEK2, NBN, BARD1, BRIP1, RAD50, RAD51C, RAD51D, … ), most studies have reported contribution of BRCA1 and BRCA2 pathogenic variants. Genetic contribution of BRCA genes has been estimated at 27% in Caucasian women. Available data from population of African origin are scarce and have mainly focused on pathogenic variants of BRCA1 and BRCA2. Reports from main studies on large sample size highlighted that BRCA1 still the major gene associated with BC in SSA. In addition, BRCA2, PALB2, and P53, are also on the top major genes with high penetrance, associated with BC. Mutation spectrum of BC genes in black African women seems to be different from Caucasian with increasing number of founder mutations identified. We hypothesis that the genetic contribution of known BC genes may be different between women of black African origin compared to Caucasians. In this review we explore the genetic contribution of known breast cancer genes in women of African origin, and discuss perspectives for prevention and patients care strategies in the era of precision medicine.